Predictive Concepts for Forecasting Air Passenger Traffic - Ekaterina V. SURKOVA; Galina A. SKACHKO; Yury MAZHAYSKIY (Communications of International Proceedings, 2021)
This article is devoted to the topical problem of forecasting passenger air traffic in conditions of instability. The idea is substantiated that it is possible to apply mathematical methods of analysis and forecasting of time series, which can act as an alternative and effective tool for predicting short-term and medium-term changes in the volume of passenger traffic, depending on the selected environmental factors. The result of the study is the proposed approach to choose a method of constructing a model for predicting the volume of regional passenger traffic by the method of trend extrapolation.
Keywords: Passenger Air Traffic; Traffic Volume; Methods Of Forecasting Passenger Traffic; Constituent Entities Of The Russian Federation.